The ethical ’boundary’ in psychopharmacology - Tempesta, Enrico; Mannelli, Paolo; Janiri, Luigi (Medicina e Morale, 1987)
Man's encounter with substances capable of producing changes in his state of consciousness, behaviour and emotional sphere is an ancient experience, dating back to the earliest forms of civilisation on our planet.